Cholinergic dysfunction-induced insufficient activation of alpha7 nicotinic acetylcholine receptor drives the development of rheumatoid arthritis through promoting protein citrullination via the SP3/PAD4 pathway - Changjun Lv; Minghui Sun; Yilei Guo; Wenxin Xia; Simiao Qiao; Yu Tao; Yulai Fang; Qin Zhang; Yanrong Zhu; Yusufu Yalikun; Yufeng Xia; Zhifeng Wei; et al. (Elsevier, 2023)
Both cholinergic dysfunction and protein citrullination are the hallmarks of rheumatoid arthritis (RA), but the relationship between the two phenomena remains unclear. We explored whether and how cholinergic dysfunction accelerates protein citrullination and consequently drives the development of RA. Cholinergic function and protein citrullination levels in patients with RA and collagen-induced arthritis (CIA) mice were collected. In both neuron-macrophage coculture system and CIA mice, the effect of cholinergic dysfunction on protein citrullination and expression of peptidylarginine deiminases (PADs) was assessed by immunofluorescence. The key transcription factors for PAD4 expression were predicted and validated. Cholinergic dysfunction in the patients with RA and CIA mice negatively correlated with the degree of protein citrullination in synovial tissues. The cholinergic or alpha7 nicotinic acetylcholine receptor (α7nAChR) deactivation and activation resulted in the promotion and reduction of protein citrullination in vitro and in vivo, respectively. Especially, the activation deficiency of α7nAChR induced the earlier onset and aggravation of CIA. Furthermore, deactivation of α7nAChR increased the expression of PAD4 and specificity protein-3 (SP3) in vitro and in vivo. Our results suggest that cholinergic dysfunction-induced deficient α7nAChR activation, which induces the expression of SP3 and its downstream molecule PAD4, accelerating protein citrullination and the development of RA.